2021
DOI: 10.2147/ceor.s334724
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Loss and Associated Costs Among Patients with Transfusion-Dependent Thalassemia in Dubai, United Arab Emirates

Abstract: Objective The aim of this study was to assess the indirect burden of patients with transfusion-dependent thalassemia (TDT) in Dubai, the United Arab Emirates (UAE). Methods Adult patients with TDT were enrolled during blood transfusion sessions. Productivity loss for patients in the preceding four weeks was reported using the validated iMTA Productivity Cost Questionnaire (iPCQ). Results A total of 161 adult patients with TDT were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The broader search across all thalassemia subtypes returned 9946 hits. However, only 13 studies on α-thalassemia (including hemoglobin H disease [HbH: deletional and/or non-deletional] and α-thalassemia with unspecified genotype) met the inclusion criteria (Figure 1) [13][14][15][16][17][18][19][20][21][22][23][24][25]. Eight studies reported on clinical burden [14,[16][17][18][19][20][21][22], two studies each reported on HRQoL [24,25] and HCRU/costs outcomes [13,15], and one study reported on both clinical burden and HCRU/costs (Table 1) [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The broader search across all thalassemia subtypes returned 9946 hits. However, only 13 studies on α-thalassemia (including hemoglobin H disease [HbH: deletional and/or non-deletional] and α-thalassemia with unspecified genotype) met the inclusion criteria (Figure 1) [13][14][15][16][17][18][19][20][21][22][23][24][25]. Eight studies reported on clinical burden [14,[16][17][18][19][20][21][22], two studies each reported on HRQoL [24,25] and HCRU/costs outcomes [13,15], and one study reported on both clinical burden and HCRU/costs (Table 1) [23].…”
Section: Resultsmentioning
confidence: 99%
“…However, only 13 studies on α-thalassemia (including hemoglobin H disease [HbH: deletional and/or non-deletional] and α-thalassemia with unspecified genotype) met the inclusion criteria (Figure 1) [13][14][15][16][17][18][19][20][21][22][23][24][25]. Eight studies reported on clinical burden [14,[16][17][18][19][20][21][22], two studies each reported on HRQoL [24,25] and HCRU/costs outcomes [13,15], and one study reported on both clinical burden and HCRU/costs (Table 1) [23]. No economic evaluations such as cost-effectiveness studies were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Employees in the UAE with thalassemia report lost productivity and absenteeism. 9 Studies in other countries highlight emotional and social problems among those with thalassemia and also possible interventions, 10 but research in the UAE is lacking. Research is also needed on support from family and community and non-government organisations.…”
mentioning
confidence: 99%